2012
DOI: 10.2174/157340312801784952
|View full text |Cite
|
Sign up to set email alerts
|

Point of Care Cardiac Ultrasound Applications in the Emergency Department and Intensive Care Unit - A Review

Abstract: The use of point of care echocardiography by non-cardiologist in acute care settings such as the emergency department (ED) or the intensive care unit (ICU) is very common. Unlike diagnostic echocardiography, the scope of such point of care exams is often restricted to address the clinical questions raised by the patient’s differential diagnosis or chief complaint in order to inform immediate management decisions. In this article, an overview of the most common applications of this focused echocardiography in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
84
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(93 citation statements)
references
References 117 publications
(118 reference statements)
1
84
0
8
Order By: Relevance
“…Point-of-care cardiac ultrasound can be very useful in these scenarios. Echocardiography in the emergency department is a well-established technique [3,6,7], butitsuseisnotascommonineveryday practice as it might be. It has been shown that FoCUS echocardiography can be a valuable tool for rapid assessment in the emergency department where predefined clinical questions can be answered with a limited number of views by noncardiologist operators [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Point-of-care cardiac ultrasound can be very useful in these scenarios. Echocardiography in the emergency department is a well-established technique [3,6,7], butitsuseisnotascommonineveryday practice as it might be. It has been shown that FoCUS echocardiography can be a valuable tool for rapid assessment in the emergency department where predefined clinical questions can be answered with a limited number of views by noncardiologist operators [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…En choque, la morbimortalidad también depende de la duración y el tratamiento rápido de la causa, sin embargo, la diferenciación clínica entre choque hipovolémico, distributivo, cardiogénico u obstructivo no siempre puede realizarse correctamente 24 , pues el examen físico solo detecta el 57% de las anomalías cardíacas 25 .…”
Section: Paro Cardíaco Y Choqueunclassified
“…Ultrasound (US) technology was integrated in the emergency department (ED) in the last decades to help the rapid identification of the etiology of diseases and to integrate physical examination, which is often not reliable enough. 2,3 Point-of-care critical ultrasound is brought to the bed of patients, images are immediately available and interpreted according with clinical symptoms and signs. It can be either multiorgan in more complex and critical conditions (cardiac arrest, unknown hypotension, shock) [4][5][6] or focal, limited, goal-directed to answer just one or few clinical questions (deep venous thrombosis, renal colic, pneumothorax).…”
Section: Introductionmentioning
confidence: 99%